PENGARUH AUDIT FEE, OPINI AUDIT GOING CONCERN, FINANCIAL DISTRESS DAN UKURAN PERUSAHAAN PADA PERGANTIAN AUDITOR PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - Astuti, Ni Luh Putu Paramita Novi; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 7 No 3 (2014), 2014)
Change of auditors of the company is the behavior of the client to make thee shift auditors. It takes the role of the auditor as an independent party to mediate internal and external parties. The purpose of the study to determine the effect of audit fees, going-concern audit opinion, financial distress and the size of the company at the turn of the auditor. To determine the sample using purposive sampling method, sample number 90 company. Data analysis is logistic regression analysis, because the dependent variabel using dummy variabels. Results of the study are audit fees, going-concern audit opinion and firm size at the turn of the auditor. Whereas no effect of financial distress the turn of the auditor.
Keywords: Change of auditors/ auditor switching, audit fees, going-concern audit opinion, financial distress and firm size.